Analisis Kinerja Manajemen Konstruksi pada Proyek Pembangunan Jakarta 2 Annex Data Center - Siswanto, Ibnu; Indriasari Indriasari; Sukadi Sukadi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The Jakarta 2 Annex Data Center construction project is one of the strategic initiatives in supporting the development of information and communication technology (ICT) infrastructure in Indonesia. This project involves a high level of complexity, both technically and non-technically, including limited workspace, strict data center quality standards, and a tight completion schedule. This study aims to analyze the performance of construction management in the Jakarta 2 Annex Data Center project, a large-scale digital infrastructure project that plays a vital role in supporting information technology services in Indonesia. The research method used is a quantitative approach, with data collected through questionnaires and interviews with project stakeholders. A total of 40 respondents, consisting of experts and project management team members, participated in the questionnaire. The analysis results indicate that the implementation of construction management functions planning, organizing, execution, and controlling has been carried out fairly well. However, several key challenges still affect performance, especially in terms of coordination and time control. This study provides strategic recommendations to improve the effectiveness of construction management through strengthening communication between teams, regular evaluations of project progress, and the implementation of more adaptive quality and time control systems.